The compass of a good place: wicht is this place? - Witzel, Ludmilla Kujat; Díaz Merino, Ximena Antonia (Travessias, 2016)
<!--[if gte mso 9]> <![endif]--> The following article aims to promote an analysis of some manifestations of the postcolonial subject voice, based on extracts from songs that make up the record “Sobre crianças, quadris, pesadelos e lições de casa (2015), from Brazilian rapper Emicida, grounded mostly in the freshness and present-day sense of his lyrics, which debates contemporary issues for the post-colonial subject. For this, Emicida’s discourse is affiliate with theory prospects from Homi Babha (1998-2005), Silviano Santiago (1978), Thomaz Bonnici (1998) and Zilá Bernd (1998). Most of all, the intention is to highlight the rapper discourse and others discourses that emerge from it, discourses understood as representations of the postcolonial subject, materialized in rap form (rhythm and poetry). <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->